Complaint Handling Performance in the Jogja Smart Service: Responsiveness and SOP Compliance - Nur Fattah, Arsianita; Asmansyah, Asmansyah; Hakim, Muhammad Lukman; Agung, Magda Faradiba Mauludia (Pinisi Business Administration Review, 2026)
The development of e-government has encouraged the use of digital applications in public services, including citizen complaint systems. The Yogyakarta City Government developed the Jogja Smart Service (JSS) to facilitate online reporting, monitoring, and resolution of public complaints. However, delays in response and several complaints that are not consistently followed up on remain. This study aims to analyze the performance of the JSS complaint service, focusing on staff responsiveness, follow-up mechanisms, and compliance with standard operating procedures (SOP). This research employed a descriptive qualitative approach, using in-depth interviews, limited observation, and document reviews of complaint records and related regulations. Data were analyzed through reduction, presentation, and conclusion drawing. The findings show that JSS improves service accessibility and simplifies complaint recording, yet responsiveness remains uneven across implementing agencies. Follow-up mechanisms function, but the duration of case resolution and documentation of evidence are not always consistent. Compliance with SOP remains partial, particularly for complaints that require cross-agency coordination. In conclusion, the JSS complaint service performs moderately effectively but requires improvements in responsiveness, standardized follow-up procedures, and stricter enforcement of SOPs. These findings provide insights for improving digital complaint management in local government.